Deep Maps and Spatial Narratives. - Bodenhamer, David J. 1947- (The Spatial Humanities Ser., 2015)
Cover -- Contents -- Acknowledgments -- Introduction: Deep Maps and the Spatial Humanities -- 1 Narrating Space and Place -- 2 Deep Geography-Deep Mapping: Spatial Storytelling and a Sense of Place -- 3 Genealogies of Emplacement -- 4 Inscribing the Past: Depth as Narrative in Historical Spacetime -- 5 Quelling Imperious Urges: Deep Emotional Mappings and the Ethnopoetics of Space -- 6 Deep Mapping and Neogeography -- 7 Spatializing and Analyzing Digital Texts: Corpora, GIS, and Places -- 8 GIS as a Narrative Generation Platform -- 9 Warp and Weft on the Loom of Lat/Long -- Conclusion: Engaging Deep Maps -- Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X.